Effects of graphene oxide sheets-zirconia spheres nanohybrids on mechanical, thermal and tribological performances of epoxy composites. Issue 15 (15th October 2018) - Che, Yuanyuan; Sun, Zhanglong; Zhan, Ruirui; Wang, Shuzhan; Zhou, Shaofeng; Huang, Jin
Abstract: In this work, graphene oxide sheets-zirconia spheres (ZrO2 -rGO) nanohybrids were fabricated by Schiff base or Michael addition reaction. Their structure was characterized by FT-IR spectroscopy, UV–vis absorption spectra, Raman spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy and atomic force microscope in detail. The reaction process of PDA-capping on rGO and APTES treatment on ZrO2 nanoparticles were verified and it was proved that the ZrO2 nanoparticles were successfully adhered onto the wrinkled surface of the graphene oxide. As a new multifunctional nanofillers, the ZrO2 -rGO nanohybrids were introduced into epoxy matrix and the mechanical, thermal properties and tribological performances of the fabricated composites were also detailedly investigated. Compared with the neat EP composites, the tensile strength and elongation at break of 0.1 wt% ZrO2 -rGO/EP are improved by 33% and 40%, respectively. Besides, the propagation of decomposition reactions in the composites could be impeded by anchoring ZrO2 nanoparticles on the lamellar skeleton of graphene oxide. Furthermore, the lubricating effect and strong interfacial interaction contributed by the ZrO2 -rGO nanohybrids result in efficient load transfer from the matrix to the hybrids, which enables the ZrO2 -rGO/EP composites to have a fairly high wear resistance performance. This novel and effective approach using ZrO2 -rGO nanohybrids as multifunctional nanofillers could be beneficial to promote the development of high performance composites.